Numerical and Experimental Studies of Wave Propagation Induced by Pile Driving - Susila, Endra; Siahaan, Suhermanto; Sinaga, Poltak; Agrensa, Fico (Institut Teknologi Bandung, 2014)
Abstract. This paper presents results of numerical and experimental studies to predict the peak particle velocity (ppv) induced by a pile driving. By utilizing a professional finite element software, Plaxis 2D Dynamic, this study analyzed ppv due to pile driving in clays for various soil stiffness and various embedded pile lengths. For verification, a full scale field test of pile driving was performed in East Kalimantan with installed instrumentations of accelerations. Results of both instrumentation and numerical analysis show that ppv depends on distance and soil rigidity. The closer the object to pile tip, the larger the ppv that will be produced. The more rigid the soils at the pile tip, the larger the ppv, too. The results also show that both field test and numerical analysis results are comparable. Finally, this paper proposes a chart to predict the ppv of soils due to pile driving in clays. The output of the proposed method is the predicted ppv for various distances from pile driving location. Abstrak. Paper ini menyampaikan hasil studi eksperimental dan numerik untuk memperkirakan besarnya kecepatan rambat gelombang (ppv) akibat pemancangan tiang pancang. Dengan bantuan software Plaxis ver. 8.2 Dynamic, studi ini menganalisis sejumlah model dengan berbagai variasi kekakuan pada tanah, khususnya tanah lempung (clay) dan berbagai kedalaman fondasi tiang tertanam. Hasil analisis software Plaxis ver. 8.2 Dynamic ini telah diverfikasi dengan hasil studi eksperimental pada sebuah proyek pemancangan fondasi tiang pancang di Kalimantan Timur. Berdasarkan analisis numerik dan data dari pengujian lapangan yang mempunyai hasil yang hampir sama, nilai ppv bergantung dari jarak dari pemancangan dan kekakuan tanah. Hasil dari penelitian ini adalah usulan formulasi prediksi besarnya kecepatan rambat gelombang (ppv) dalam bentuk chart untuk mempermudah menentukan nilai ppv yang akan terjadi akibat pemancangan di tanah lempung. Sedangkan keluarannya akan berupa besaran nilai ppv (peak particle velocity) terhadap jarak pemancangan tiang.